2019
DOI: 10.3390/su11154211
|View full text |Cite
|
Sign up to set email alerts
|

Plant Biodiversity Knowledge Varies by Gender in Sustainable Amazonian Agricultural Systems Called Chacras

Abstract: Chacras, which are Amazonian agricultural systems, are examples of traditional agricultural management that are sustainable. They are also characteristic of the identities of different ethnographic groups in tropical America. However, information regarding the botanical characterization of chacras is scant. In tropical rural communities, there is a gender bias hypothesis that makes women potential reservoirs of traditional chacras plant knowledge. We present an experimental study in order to demonstrate if thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
2
14
0
9
Order By: Relevance
“…These practices were never registered and could offer significant progress in various medical fields [81]. Conservation of this traditional knowledge must be taken into account [82] and is a priority according to several international agreements [83]. Perhaps the first milestone is given by the Declaration on the Rights of Indigenous Peoples (2007), [84] (p. 10) in which the UN included the following text:…”
Section: Context Of the Fddmentioning
confidence: 99%
“…These practices were never registered and could offer significant progress in various medical fields [81]. Conservation of this traditional knowledge must be taken into account [82] and is a priority according to several international agreements [83]. Perhaps the first milestone is given by the Declaration on the Rights of Indigenous Peoples (2007), [84] (p. 10) in which the UN included the following text:…”
Section: Context Of the Fddmentioning
confidence: 99%
“…Also, in this issue Luzuriaga-Quichimbo et al studied traditional plant knowledge in Chacras, which are traditionally managed Amazonian agricultural systems. They found that this plant biodiversity knowledge varies by gender concluding that gender perspective must be taken into account in biodiversity conservation programs [38].…”
Section: Sustainability Biodiversity and Indigenous Knowledgementioning
confidence: 99%
“…Currently, approximately 40% of Earth's surface is under use for food and fiber production and this is anticipated to continue to rise. This trend will have grave consequences for the environment and biodiversity unless traditional agroecosystems like the Amazonian Chacras described in this issue are preserved [38,42,43]. In addition, regenerative sustainable agriculture techniques must be promoted, but in a way that avoids external or government enforcement.…”
Section: Biodiverse Agriculturementioning
confidence: 99%
“…We will also take into account the familiarities of men and women, as previous studies show that this is a differentiating factor in terms of the identity traits of a place [15] because, traditionally, the roles of each of the genres have been different. Women have always been associated with the field of home and childcare and parenting, while men spent less time in the house and used to perform jobs associated with agriculture and livestock maintaining a more direct relationship with the natural environment.…”
Section: Introductionmentioning
confidence: 99%